A review and future agenda for behavioral research on leader–follower interactions at different temporal scopes. (26th November 2021) - Hemshorn de Sanchez, Clara Sofie; Gerpott, Fabiola H.; Lehmann‐Willenbrock, Nale
Summary: Scholars are increasingly embracing innovative research designs and measures to capture actual leader and/or follower behaviors in real interactions. Our systematic review of this emerging research stream and development of a research agenda seeks to move the literature further in this direction. Specifically, we aim to inspire scholars with techniques for observing, manipulating, or training actual leadership and/or followership behaviors at different temporal scopes in the laboratory or field and identify which future research areas are worth exploring. To achieve these aims, we perform a review of existing studies in this domain according to their underlying conceptual model and temporal scope. We analyze which types of leader or follower behaviors (i.e., verbal behavior, text‐based behavior, choice behavior, gaze, facial expressions, gestures, voice tone and pitch, movement cues, and unspecified nonverbal behavior) have been studied, how they have been studied (i.e., using which methodological approaches), and in which study context (i.e., laboratory or field). We distill these findings to derive six future research directions: conducting studies that connect actual and perceived leader/follower behaviors, considering temporal granularity in a nuanced manner, exploring interdependent behavioral patterns, leveraging unconventional research methods, performing multimodal behavior analyses, and conducting more studies "in the wild" (i.e., field research).